Efektivitas Larvasida Temefos Dengan Konsentrasi Berbeda Terhadap Kematian Larva Aedes Aegypti Di Tiga Desa Endemis Demam Berdarah Dengue Kota Banda Aceh - Riski Muhammad; Asmawati Asmawati; T. M. Rafsanjani; Husna Husna; Diza Fathamira Hamzah (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2022)
Almost all villages in Banda Aceh City are one of the endemic areas for Dengue Hemorrhagic Fever. Various efforts have been made to reduce dengue cases by means of fumigation and larvicides. This study aimed to determine the differences in the effectiveness of temefos larvicides with different concentrations on the mortality of Ae. aegypti in three dengue endemic villages in Banda Aceh City, namely Punge Blang Cut, Ateuk Pahlawan and Jeulingke villages. The research method used is a laboratory experiment with one control and three replications with a post test only design with a control group. Isolate Ae. aegypti was obtained by installing ovitrap in 10 houses from 3 endemic villages. The collected eggs are hatched and maintained until the first generation (F1) is then measured for effectiveness (resistance) status. The results of the study at concentrations of 0.05 gram/liter and 0.1 gram/liter had high resistance, while the concentration of 0.2 gram/liter isolates from Punge Blang Cut was moderate (moderate) resistant and isolates from Ateuk Pahlawan and Jeulingke were high resistant. It is necessary to monitor and evaluate the use of larvicides through resistance monitoring efforts so that every activity carried out can be successful. And it is also necessary to carry out other control efforts or other combinations of control to reduce cases of Dengue Hemorrhagic Fever in Banda Aceh City.